Enhanced Plant Growth Through Composite Inoculation of Phosphate-Solubilizing Bacteria: Insights from Plate and Soil Experiments - Mengsha Li; Xinjing Li; Daosheng Xue; Chengjiang Bao; Keying Zhang; Lili Chen; Qiuping Li; Rui Guo (Agronomy)
Excessive application of phosphorus (P) fertilizers does not alleviate P deficiency in soils and may cause water eutrophication. The available P in acidic soils is bound to minerals, such as iron and aluminum, in forms that are difficult to utilize by plants. The low availability of P is detrimental to soil health and crop growth. To address the P imbalance in the soil, different bioremediation techniques, such as phosphate-solubilizing bacteria (PSB) application, have been employed. However, the systematic analysis of the effects of composite inoculation of PSB on crops remains elusive. In this study, the effects of composite-inoculated PSB on plant growth were systematically evaluated by two scales: plate experiment and soil test. This study employed six different strains of PSB including Lelliottia amnigena 1-1 (A), Kluyvera intermedia 1-2 (B), Pseudomonas tolaasii 1-6 (C), Burkholderia cepacia 2-5 (D), Pseudomonas frederiksbergensis 2-11 (E), and Pseudomonas rhodesiae 2-47 (F). Among the 57 different combinations of these strains, four combinations (AE, AF, ADF, and AEF) indicated higher phosphate-solubilizing abilities than the single strains. These combinations were used for subsequent experiments. The plate experiment revealed that composite strains were more effective than single strains in promoting the growth and development of seedlings and roots of oilseed rape. Furthermore, AE, AF, and AEF combinations indicated excellent growth-promoting effects. Moreover, the soil test revealed that the composite inoculation of AE and AEF significantly enhanced biomass accumulation and root development in oilseed rape. The increased growth-promoting effects of the composite strains were observed to be associated with to their phosphate-solubilizing capacities. Both scales confirmed that compared to single inoculation, composite inoculation of PSB is more beneficial for plant growth. This study provides composite inoculation materials and foundational data to support the bioremediation of P imbalance in soil.